2020
DOI: 10.1155/2020/8821289
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette or Vaping Product Use-Associated Lung Injury (EVALI) Mimicking COVID-19 Disease

Abstract: Background. Coronavirus 2 (SARS-CoV-2) is the virus associated with the coronavirus disease (COVID-19) causing a pandemic worldwide in 2020. There are other noninfectious diseases that can present exactly as COVID-19, and the management and approach are completely different, hence the importance of understanding and having a wide differential in patients presenting with similar characteristics. Case Report. A 23-year-old male, with a history of childhood asthma, presented to the Emergency Department in a hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Heightened odds of self-reported COVID-19 infection among dual tobacco users could be due to the fact that dual users were exposed to elevated levels of nicotine and toxicants via cigarette smoking and vaping, which adversely affects lung function [13,14], thus leading to a significant increase of susceptibility to COVID-19 infection compared to single product users. While we only found a significant association of self-reported COVID-19 infection for dual users, other studies have found an association between exclusive cigarette or e-cigarette use, respectively, with more severe COVID-19 progression [6,7,12].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Heightened odds of self-reported COVID-19 infection among dual tobacco users could be due to the fact that dual users were exposed to elevated levels of nicotine and toxicants via cigarette smoking and vaping, which adversely affects lung function [13,14], thus leading to a significant increase of susceptibility to COVID-19 infection compared to single product users. While we only found a significant association of self-reported COVID-19 infection for dual users, other studies have found an association between exclusive cigarette or e-cigarette use, respectively, with more severe COVID-19 progression [6,7,12].…”
Section: Discussioncontrasting
confidence: 94%
“…Sufficient evidence shows using e-cigarettes, or vaping, is harmful to lung function [ 10 , 11 ]. Both cigarette and e-cigarette use damage the respiratory system [ 10 , 12 ], potentially increasing the risk of experiencing COVID-19-related measures, such as symptoms and diagnosis. This poses an alarming risk for dual users as they might suffer elevated health risks from the use of use multiple tobacco products and increase their susceptibility to infection and result in worse prognosis once infected [ 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even second-hand EC exposure was associated with higher odds of reporting an asthma attack in adolescents [ 104 ] and children [ 105 ]. Additionally, several cases of EVALI (some of them mimicking COVID-19) were recently reported in patients with a history of asthma [ 49 , 62 , 106 , 107 , 108 , 109 ]. Asthma is more common in patients with EVALI (approximately 30%; 43.6% in adolescents and 28.3% in adults) compared to the 8% to 10% of the general population [ 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…EC devices can contain cannabis-based products including tetrahydrocannabinol (THC), the psychoactive component of cannabis (marijuana) [ 18 ]. Several asthmatics have suffered from EVALI after the use of such devices [ 49 , 107 , 108 ]. Two more cross-sectional studies have demonstrated the association between EC and cannabis [ 66 , 110 ], whereas another cross-sectional study has shown the opposite [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“… 47 Although vaping-related illness may have nearly disappeared as a consequence of increased public awareness resulting in risk reduction by users and by removal of vitamin E acetate from vaping products, a case report of a patient in April 2020 reminds clinicians that EVALI should remain in the differential diagnosis for young patients admitted with severe lung injury. 48 Presenting symptoms of EVALI (dyspnea, cough, fever, nausea, vomiting, and diarrhea) overlap with those of COVID-19, 36 , 49 , 50 and during population surges of the pandemic there is a tendency to narrow diagnostic considerations. As noted previously, EVALI is considered a diagnosis of exclusion, particularly exclusion of infectious etiologies, but critical to making the diagnosis is asking patients about vaping exposures.…”
Section: Vaping and Covid-19mentioning
confidence: 99%